Push! Dig! Scoop! - Greene, Rhonda Gowler,Kirk, Daniel (Bloomsbury Publishing USA, 2017)
Cover – Title – Copyright – Dedication – Back Ad.
Description based on publisher supplied metadata and other sources
Keywords: Stories in rhyme; Construction equipment-Fiction; Counting; Trucks-Fiction; Electronic books